2016
DOI: 10.1097/hnp.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Perceptions of Futile Care

Abstract: Health care professionals believe that futile care must not be provided; however, there is no clear agreement over the definition and the manifestations of futile care. The aim of this study was to explore Iranian nurses' perceptions of futile care. In this qualitative exploratory study, the conventional content analysis approach was used for collecting and analyzing the study data. Three main themes were extracted from the data: nonfutility of care: care tantamount with outcome; sense of burnout; and subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
1
13
0
1
Order By: Relevance
“…The frequent occurrence of these consequences over the years has tended to foster a negative attitude towards admission and hospitalisation of elderlies with advanced diseases. In line with our findings, previous studies found that the perception of futile care hurts caring behaviours of ICU caregivers toward elderly patients [22], [23], [24], [25].…”
Section: Discussionsupporting
confidence: 93%
“…The frequent occurrence of these consequences over the years has tended to foster a negative attitude towards admission and hospitalisation of elderlies with advanced diseases. In line with our findings, previous studies found that the perception of futile care hurts caring behaviours of ICU caregivers toward elderly patients [22], [23], [24], [25].…”
Section: Discussionsupporting
confidence: 93%
“…In some countries with universal healthcare coverage, the physician may decide whether care is futile or not, opting to withdraw or sustain life support without the family or patient's consent, creating ethical dilemmas (Luce & White, ). Moral distress and burnout among nurses providing care to patients receiving futile care when comfort measures should be pursued is well documented in the literature; often nurses feel passionately the care is brutal and malicious (Aghabarary & Nayeri, ; Catlin et al., ; Ferrell, ; Meltzer & Huckabay, ; Özden et al., ; Yekefallah, Ashktorab, Manoochehri, & Hamid, ). Instances where the ethical dilemmas are significant, whether felt by the family, patient or healthcare team, can result in litigation (Fontugne, ; Stewart, ).…”
Section: Resultsmentioning
confidence: 99%
“…Relating to Q3 about dealing with challenges of staff and management, the participants mentioned lack of privacy, tough schedule, management favouritism, communication gap, peer conflicts and less experienced staff and administration, which accede with past literature (Aghabarary and Nayeri, 2016;Rostami et al, 2019):…”
Section: Prrmentioning
confidence: 84%